HPLC Method for the Determination of Pioglitazone in Human Plasma and Its Application to Pharmacokinetic Study - ALIM, MUHAMMAD; NAWAZ, RAKHSHANDA; SHAHID*, MUHAMMAD; RAFIQUE ASI†, MUHAMMAD; IQBAL, TAHIRA; ANWAR, FAROOQ (Asian Journal of Chemistry, 2009)
For the quantification of pioglitazone in human plasma a validated HPLC method was developed using ultraviolet detection. Chromatographic separation of pioglitazone in plasma was achieved on a C18 column. Mixture of acetonitrile and (0.1 M) ammonium acetate (41:59) having pH (4.10) was used as a mobile phase. Piroxicam was used as an internal standard. The calibration curve was linear over the range 0.055-2.0 μg/mL in human plasma (r2 = 0.9986). After oral administration of pioglitazone (30 mg) to male volunteers, the plasma concentrationtime curve of pioglitazone was best conformed to two-compartment open model. The maximum concentration (Cmax) 0.86 μg/mL was achieved at the peak concentration time (tmax) 2.40 h. AUC0-24 of pioglitazone was observed 7.71 h μg/mL. Total body clearance, volume of distribution and elimination rate constant of pioglitazone after oral administration were 4.84 L/h, 52.48 L and 0.45 L/h, respectively.